Trade unions and social movements at the crossroads: a Portuguese view - Costa, Hermes Augusto (2019)
As a result of the international economic crisis that has significantly affected the peripheral countries of the eurozone, austerity became an overwhelming issue, able to potentiate new synergies between trade union movement and other social movements. Especially between 2011 and 2015, Portugal faced a new wave of mobilizations in which the new “post-materialist” guidelines, such as social movements with an identity nature (environmentalism, feminism, LGBT movements, ethnic minorities, etc.), have become blurred, leading to a resurgence of old “materialist” values centred on employment issues and protection of labour rights. We characterize the discourses of the old trade union actors who have historically defended labour rights (CGTP and UGT) but also the newly emerging socio-labour movements: like FERVE (Fartos Destes Recibos Verdes, Fed up of these green receipts), MayDay network, Precários Inflexíveis (Precarious Inflexible Workers) and Movement of the unemployed (Movimento Sem Emprego). Moreover, we analyse the “traditional” episodes of social conflict (strikes) as well as “innovative” broader social protests aiming to denunciate austerity and defend the Social state. By doing this, the basis for alliances between unions and social movements, and the old tensions and cleavages between them, are at stake.